TI_GERICHTE 52.2018.227 vom 26. März 2018 , Stima ufficiale della sostanza immobiliare. Aggiornamento intermedio - TI Tribunale d'appello (2018)
Stima ufficiale della sostanza immobiliare. Aggiornamento intermedio